Flavor characterization of native Peruvian chili peppers through integrated aroma fingerprinting and pungency profiling. (July 2018) - Morales-Soriano, Eduardo; Kebede, Biniam; Ugás, Roberto; Grauwet, Tara; Van Loey, Ann; Hendrickx, Marc
Abstract: A broad range of Peruvian chili peppers are available but not properly characterized. To increase the insight into their flavor compounds, a head space GC–MS fingerprinting (volatiles) and an HPLC-based profiling approach (pungency) was implemented to characterize twenty landraces ( Capsicum annuum, C. baccatum and C. chinense ). The data obtained was analyzed with powerful chemometric approaches to identify unique flavor compounds for each of the species and for each of the landraces within a specific species. The pungency profile and volatiles such as esters, terpenes and norcarotenoids distinguish Cerezo triangular (4) ( C. annuum ). Mainly esters provoked the separation between Chico (42), Cacho de cabra rojo (323), Amarillo de Chachapoyas (318) ( C. baccatum ), Arnaucho (60) and Miscucho amarillo (69) ( C. chinense ). This study demonstrates the potential of the integrated fingerprinting, profiling and a chemometric approach to extensively understand the unique flavor compounds in Peruvian chili peppers. Graphical abstract: Highlights: Integrated chemometric approach was essential to identify unique flavor compounds. Pungency, terpenes, norcarotenoids and esters provoked the separation in C. annuum . Esters mainly distinguish landraces in C. baccatum and C. chinense . Results might be a starting point for the design of chili pepper based products.